Mental Contrasting and Transfer of Energization. (February 2014) - Sevincer, A. Timur; Busatta, P. Daniel; Oettingen, Gabriele
Mental contrasting a desired future with present reality is a self-regulation strategy that fosters energization in line with a person's expectations of successfully attaining the desired future. We investigated whether physiological energization (measured by systolic blood pressure) elicited by mental contrasting a desired future of solving a given task transfers to effort in an unrelated task. As predicted, mental contrasting a desired future of excelling in an intelligence test (Study 1) and of writing an excellent essay (Study 2) triggered changes in energization that translated into physical effort in squeezing a handgrip (Study 1) and translated into mental effort in writing a get-well letter (Study 2). Results suggest that mental contrasting of solving one task triggers energization that may fuel effort for performing an unrelated task. Implications for intervention research are discussed.